Comparison of short-term outcome between diverting colostomy and colonic stent as a bridge to surgery for left colonic malignant obstruction. Issue 14 (April 2020) - Jung, Won Beom; Shin, Jin Yong; Park, Jong Kwon
Abstract : Abstract: The self-expanding metallic stent (SEMS) has been comprehensively investigated as a bridge to surgery. SEMS enables the control of acute colonic obstruction. However, comparison between SEMS and diverting colostomy as another bridge procedure was still challenging issue. Thus, the aim of this study was to compare these 2 procedures. In this retrospective cohort study, patients who received diverting colostomy and SEMS for acute left colonic obstruction between February 2016 and August 2018 were included. They were classified into the colostomy group (n = 27), including 5 patients who had SEMS failure previously, and the SEMS group (n = 23). The clinicopathologic parameters, pathologic results, and short-term outcomes were compared. No significant differences were found in clinicopathologic characteristics and complication rates between the 2 groups. After the bridge procedures, the SEMS group showed a higher rate of laparoscopic colonic resection than the colostomy group (100% vs 76%, P = .023). The colostomy group showed a higher rate of rectal cancer (24.0% vs 9.1%, P = .019) and later recovery of flatus (3 vs 2 days, P = .011) than the SEMS group. Additionally, the length of resected colon was longer in the colostomy group than in the SEMS group (33.9 vs 23.4 cm, P = .007). Although SEMS might permit higher laparoscopic resection rates and faster recovery of bowel habits than diverting colostomy, SEMS showed meaningful failure rate including migration and perforation. In addition, diverting colostomy showed acceptable complication rates and feasible performance. An individualized approach is necessary considering the advantages and disadvantages of both procedures.